Management of Kawasaki disease in the British Isles. - Dhillon, R (1993)
Kawasaki disease in the British Isles was surveyed by an active reporting scheme, based on all cases reported to the British Paediatric Surveillance Unit that were diagnosed between 1 January and 31 December 1990. The study was prompted by the need to investigate the high case fatality rate of Kawasaki disease of 2% observed in 1988. One hundred and sixty three patients were identified of whom six (3.7%) died. Forty five children (28%) suffered cardiac complications of which 39 (24%) were coronary artery abnormalities; five children were diagnosed at postmortem examination, and coronary artery abnormalities were detected by echocardiography in 34. One hundred and forty nine children (93%) had echocardiography. High thrombocytosis, leucocytosis, duration of fever, and younger age were associated with the presence of coronary artery abnormalities. Erythrocyte sedimentation rate, sex, and the number of diagnostic criteria were not. One hundred and thirty three children (87%) received aspirin. Ninety three children (61%) received intravenous gammaglobulin (IVGG). Children were more likely to receive IVGG if they had thrombocytosis or typical Kawasaki disease. The incidence of coronary artery abnormalities was found to be similar in those treated with IVGG (29%) and those untreated (20%), including those treated within 10 days of onset. This may have reflected selection of the more serious cases to receive IVGG or that Kawasaki disease in the British Isles is a different illness to that experienced elsewhere. It amy be, however, that IVGG is less effective in the treatment of British patients with Kawasaki disease than has been the experience in the United States and Japan. These observations emphasise the need for a therapeutic trial of treatment modalities for Kawasaki disease in the UK and the Republic of Ireland.